Structural parts

By employing ultra-high tensile materials with optimized surface roughness and curvature radii in structural components, the challenges of low molding limits and fatigue failure are addressed, enhancing the fatigue durability of components like automobile chassis parts.

JP7659222B1Active Publication Date: 2025-04-09NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025506056
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-14
Filing Date
2024-06-14
Publication Date
2025-04-09
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

Conventional ultra-high tensile materials have low molding limits, making it difficult to mold bent portions with small radii of curvature, which leads to surface roughness and fatigue failure in structural components like automobile chassis parts.

Method used

The use of ultra-high tensile materials with superior molding limits, specifically high-Si and low-Si types, where the surface roughness and radius of curvature of the bent portions are optimized within specific ranges to suppress fatigue cracking and improve durability.

Benefits of technology

This approach effectively suppresses the deterioration of fatigue durability caused by surface roughness and bending shape inside the bend, resulting in improved fatigue properties and increased durability of structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659222000004
    Figure 0007659222000004
  • Figure 0007659222000005
    Figure 0007659222000005
  • Figure 0007659222000006
    Figure 0007659222000006
Patent Text Reader

Abstract

A structural component made of a steel plate, the structural component having a flat plate portion 10a and a bent portion 10b, the bent portion 10b satisfying the following formulas (1), (2) and (3). 28≦√area≦45 (1) 0.17≦r / t≦6.90 (2) 0.22≦n' (3) however, √area is the square root of the projected area of ​​the micro defect on the inside of the bent part 10b [μm] r is the minimum value of the inner curvature radius of the bend 10b [mm] t is the thickness of the flat plate portion 10a [mm] n' is the interquartile range of the nano hardness of the flat plate portion 10a / mean nano hardness It is.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a structural component. [Background technology]

[0002] It has been proposed to make it difficult for fatigue cracks to occur on the burred end surface by setting the arithmetic mean roughness on the burred end surface to a predetermined value or less (see Patent Document 1). It has also been proposed to provide a metal formed sheet in which the arithmetic mean surface roughness on the convex side surface of the minimum sheet thickness part of the ridge line of the design surface is set to a predetermined value or less, thereby suppressing the occurrence of surface roughness on the convex surface of the ridge line (see Patent Document 2). It has also been proposed to apply the √area parameter model to quantitatively evaluate the effect of surface roughness on fatigue strength (see Non-Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 7036298 [Patent Document 2] Patent No. 6954211 [Non-patent literature]

[0004] [Non-Patent Document 1] Takayoshi Murakami, Koji Takahashi, and Akio Yamashita, "Quantitative Evaluation of the Effect of Surface Roughness on Fatigue Strength," Transactions of the Japan Society of Mechanical Engineers (Series A), Vol. 63, No. 612 (1997), pp. 1612-1619 Summary of the Invention [Problem to be solved by the invention]

[0005] For example, the application of ultra-high tensile steel to automobile chassis components has the great advantage of reducing the weight of parts, etc. However, the increased strength caused by the use of ultra-high tensile steel tends to reduce formability, so by identifying the limits of the material and appropriately designing the part shape, the benefits of using ultra-high tensile steel can be maximized.

[0006] In the case of chassis parts such as lower arms, structures with bent parts such as M-shaped cross sections are adopted so that the necessary rigidity can be ensured even with thinning by using high-strength materials. From the viewpoint of increasing the degree of freedom when arranging the necessary structural parts in a limited space and avoiding interference between parts, it is desirable to make the radius of curvature on the inside of the bend as small as possible. Also, in cases such as inserting a cylindrical bush into the outer diameter of a cylindrical shape formed by burring, it is desirable to make the radius of curvature on the inside of the bend as small as possible in order to extend the fitting length within the limited space.

[0007] However, when bending with a small radius of curvature that exceeds the material's limit, there is a problem that surface roughness such as microcracks occurs on the inside of the bend. As a result, fatigue failure occurs starting from the surface roughness, and sufficient fatigue durability cannot be obtained. Conventional ultra-high tensile steel has a problem that it is impossible to form a bent part with a small radius of curvature because of its low forming limit. In addition, the limit value of the curvature radius that does not impair fatigue durability varies depending on the material, and there was also a problem that the correlation between the structure of the bent part and the material was not clear.

[0008] None of the techniques described in the above patent documents focuses on the surface roughness on the inside of the bend, and it is difficult to suppress the decrease in fatigue durability caused by the surface roughness on the inside of the bend.

[0009] Therefore, an object of the present invention is to provide a structural component capable of suppressing a decrease in fatigue durability caused by the surface roughness on the inside of the bend and the shape of the inside of the bend. [Means for solving the problem]

[0010] The present disclosure has been made based on the above findings, and its gist is as follows.

[0011] (1) A structural component constructed from steel plates, A flat portion and a bent portion are included. A structural component, wherein the bent portion satisfies the following formulas (1), (2), and (3). 28≦√area≦45 (1) 0.17≦r / t≦6.90 (2) 0.22≦n' (3) however, √area is the square root of the projected area of ​​the micro defect on the inside of the bent part [μm] r is the minimum radius of curvature on the inside of the bend [mm] t is the thickness of the flat part [mm] n' is the interquartile range of the nanohardness of the plate / mean nanohardness It is.

[0012] (2) The structural part according to the above (1), further satisfying the following formula (1)' and formula (2)'. 33≦√area≦44 ··(1)' 0.17≦r / t≦3.45 (2)'

[0013] (3) A structural component according to (1) above, wherein the flat portion has a Vickers hardness of 310 or more.

[0014] (4) A structural component as described in (1) above, wherein the flat portion has a Vickers hardness of 340 or more.

[0015] (5) The structural part according to any one of (1) to (4) above, further satisfying the following formula (9): 33≦√area≦1.05{0.0976( r / t)) 3 -0.7185 (r / t) 2 -1.0542(r / t)+43.426} ··(9) Effect of the Invention

[0016] The present invention has an effect of providing a structural component capable of suppressing a decrease in fatigue durability caused by the surface roughness on the inside of the bend and the shape of the inside of the bend. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram showing an automobile suspension part as an example of a structural part according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view taken along dashed line II' in FIG. [Diagram 3] FIG. 13 is a diagram showing five images of the inside of a bent portion that have been captured and linked together. [Figure 4] FIG. 1 is a characteristic diagram showing a method for evaluating surface roughness by converting a curved surface into a flat surface. [Diagram 5] FIG. 13 is a diagram showing a schematic diagram of the surface roughness on the inside of a bend represented by the characteristic C3. [Figure 6] 13 is a histogram showing the distribution of nano-hardness of a high Si type. [Figure 7] 1 is a histogram showing the distribution of nano-hardness of a low-Si type. [Figure 8] FIG. 1 is a characteristic diagram showing the distribution of uniform elongation u-El (vertical axis) of high Si type and low Si type, and the value n' (horizontal axis) obtained by dividing the interquartile range by the average nanohardness. [Figure 9] FIG. 1 is a characteristic diagram in which √area and r / t are plotted for each of Examples 1 to 10 of the present invention and Comparative Examples 1 to 10 shown in Table 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, some embodiments according to the present disclosure will be described with reference to the drawings. However, these descriptions are intended to merely exemplify preferred embodiments of the present disclosure, and are not intended to limit the present disclosure to such specific embodiments. The description will be given in the following order. 1. Overview of this Disclosure 2. Effect of small defects on the inner surface of bent steel on fatigue strength 3. Structural components according to the present disclosure 4. Method for evaluating surface roughness on the inside of a bend 5. High Si type and low Si type 6. Working Example

[0019] 1. Overview of this Disclosure For example, structural parts for automobiles (parts that constitute structures) are becoming stronger year by year, and as the strength increases, the weight is being reduced by thinning. In order to realize lightweight and highly functional structural parts, it is important to combine "lightweight parts by high-strength thinning" and "structural design to utilize the strength characteristics of steel". For example, in high-strength thin-walled chassis parts (e.g., suspension parts such as lower arms), which are structural parts for automobiles, fatigue cracks may occur due to the decrease in rigidity caused by thinning and the decrease in surface properties (surface roughness) caused by processing, and the fatigue properties of the parts may deteriorate. In particular, when a structural part includes a bent part that has been bent, the inner side of the bend of the bent part is subjected to compressive deformation, so the surface properties are reduced compared to before processing, and the surface roughness leads to the deterioration of fatigue properties. Chassis parts are important safety parts, and are constantly subjected to vibration and load, so it is essential to improve fatigue durability. In this embodiment, a structural part that suppresses the occurrence of fatigue cracks from the inner side of the bend is provided by an appropriate combination of material and part structure (especially the surface roughness of the inner side of the bend and the bend shape).

[0020] In this disclosure, by using an ultra-high tensile material (tensile strength of 980 MPa or more) with a better forming limit than conventional materials, deterioration of the surface roughness on the inside of the bend of a bent part of a press-formed product with an M-shaped cross section is suppressed to make the surface smooth, enabling forming with a smaller radius of curvature on the inside of the bend. Furthermore, the relationship between the range of the radius of curvature on the inside of the bend that satisfies fatigue durability and the material properties is clarified.

[0021] As a result of intensive research, the inventors have found that by applying an ultra-high tensile steel having a better forming limit than conventional steels, and when the parameters of the bent portion, specifically the surface roughness on the inner side of the bend and the radius of curvature on the inner side of the bend, satisfy certain conditions, fatigue cracks occurring in the bent portion can be suppressed. The material properties affect the change in surface roughness before and after processing of the bent portion. It is possible to improve fatigue durability by managing the appropriate surface properties of the bent portion by the material and the shape (design) of the bent portion. Compared to conventional steels, the steel having a better forming limit according to this embodiment is less likely to have large surface roughness on the inner side of the bend after processing (i.e., unevenness is less likely to develop), improving fatigue durability. The larger the radius of curvature on the inner side of the bend, the less likely the surface roughness on the inner side of the bend becomes.

[0022] The ultra-high tensile steel with excellent forming limits according to the present disclosure is a high-Si type with a relatively high Si content and a low-Si type with a relatively low Si content. The two types have different mechanisms for improving fatigue durability. The high-Si type has a relatively large surface roughness due to the presence of Si-derived scale, but the n-value (work hardening index) related to formability is high, so microcracks are less likely to develop on the inside of the bend. For this reason, in the high-Si type, folding of the compressed part on the inside of the bend is suppressed during bending, thereby realizing high durability. On the other hand, the low-Si type has a relatively low n-value, but the surface roughness derived from the Si scale is small, which suppresses the development of microcracks on the inside of the bend. For this reason, in the low-Si type, the occurrence of fatigue cracks is suppressed by taking advantage of the excellent surface smoothness, and high durability can be realized.

[0023] As a result of extensive investigations, the inventors came up with the idea of ​​setting the range of parameters for each steel type by incorporating the difference in the mechanism of fatigue cracking between high-Si and low-Si types. In this disclosure, a suitable parameter range will be described for the case of using high-Si ultra-high tensile steel out of the high-Si and low-Si types.

[0024] 2. Effect of small defects on the inner surface of bent steel on fatigue strength The present inventors have thoroughly studied the effect of the square root of the projected area of ​​a minute defect on the inner side of a bent portion, √area, on fatigue strength, and have concluded that the fatigue limit σ W Since is expressed by the following formula (4) using √area and Vickers hardness, we focused on √area as a characteristic value that affects fatigue durability. Note that micro defects may refer to unevenness on the surface of a press-formed body. In inferior cases, micro defects may be observed as cracks rather than simply unevenness. σW=[1.43(HV+120){(1-R) / 2} α ] / (√area) 1 / 6 (4) however, σW: Fatigue limit [MPa] HV: Vickers hardness [HV kgf / mm 2 ] α: 0.226+HV×10-4 R: Stress ratio (σmin / σmax) It is.

[0025] √area [μm] is calculated from the following formulas (5) and (6) based on the description in the above Non-Patent Document 1. In formulas (5) and (6), a [μm] is the roughness height (maximum height Rz), and 2b [μm] is the roughness pitch (average element length, wavelength Rsm of the height waveform).

[0026]

number

[0027]

number

[0028] 3. Structural components according to the present disclosure In the bent portion, the larger the value of √area, the greater the surface roughness, and therefore the lower the fatigue durability of the structural component. Also, the smaller the value of r / t, the ratio of the curvature radius on the inside of the bend to the plate thickness of the steel plate, the lower the fatigue durability of the structural member. The inventors have thoroughly studied the relationship between √area and r / t of the structural component and the fatigue properties of the structural component, and have found that when √area and r / t are within a specified range, the fatigue durability can be improved compared to the conventional case.

[0029] FIG. 1 is a diagram showing an automobile suspension part as an example of a structural part according to the present disclosure, and more specifically, a diagram showing a lower arm 10 of a suspension. FIG. 2 is a diagram showing a cross section along the dashed line I-I' in FIG. 1. The structural part according to the present disclosure is not limited to use in automobiles. The lower arm 10 is subjected to pressing, burring, etc., and has a flat plate part (top plate part) 10a and a bent part 10b. FIG. 2 shows an M-shaped cross section including the flat plate part 10a and the bent part 10b. The present inventors have found that the fatigue properties can be improved compared to conventional products by satisfying the following formulas (1), (2), and (3), and more preferably by satisfying the formulas (1)', (2)', and (3). 28≦√area≦45 (1) 0.17≦r / t≦6.90 (2) 0.22≦n' (3) 33≦√area≦44 ··(1)' 0.17≦r / t≦3.45 (2)' however, √area: Square root of the projected area of ​​the micro-defect on the inside of the bent portion 10b (parameter indicating the roughness of the surface after processing) [μm] r: minimum value of the inner curvature radius of the bent portion 10b [mm] t: thickness of the flat plate portion 10a [mm] n': Interquartile range of nano hardness of the flat plate portion 10a / average nano hardness It is.

[0030] For example, the flat portion 10a is a portion in which the thickness reduction from the thickest portion is within 10% and which is not significantly distorted by bending. The flat portion 10a may be a portion having the same thickness as the material.

[0031] As described above, the inventors have thoroughly studied the values ​​of √area and r / t described in Non-Patent Document 1 when bending portions are formed using ultra-high tensile steel, which has a better forming limit than conventional steels, and have found that by specifying the values ​​of √area and r / t within predetermined ranges, it is possible to improve fatigue properties compared to conventional steels.

[0032] In addition, the structural component according to the present disclosure has a bent portion formed by press molding, burring processing, or the like. As an example of a processing method for forming the bent portion, bending may be performed with the inner surface of the bent portion in close contact with a die. For example, by conducting a test in advance and determining the conditions for bending (e.g., inner bend R, die clearance, etc.), it becomes possible to perform bending with the inner surface of the bent portion in close contact with the die. This makes it difficult for the surface roughness of the inner bend to increase, and increases fatigue durability. In addition, since the value of √area of ​​the ground structural component is about 6.9, it does not satisfy formula (1), and the structural component according to the present disclosure does not include a ground product.

[0033] 4. Method for evaluating surface roughness on the inside of a bend When evaluating the surface roughness of the inner side of the bent portion 10b, the curved surface is converted to a flat surface to evaluate the surface roughness. For this purpose, a cross-sectional sample of the bent portion 10b with a mirror finish is prepared with a cross section perpendicular to the surface of the flat portion 10a (i.e., the cross section shown in FIG. 2) as the measurement surface, and five images of the inner side of the bent portion 10b are taken at a magnification of 500x using an optical microscope, and the five images 20 are linked as shown in FIG. 3. Then, the "find edges" function of the image processing software (imageJ) is used to extract the contours of the surface irregularities from the difference in pixel values, and the "Analyze Line Graph" function is used to output them as (x, y) coordinates (units: μm). If the structural part is painted with electrocoating or the like, the paint is removed before the images are taken.

[0034] 4 is a characteristic diagram showing a method for evaluating surface roughness by converting a curved surface into a flat surface using the output coordinates (characteristic C1). A Gaussian filter of σ=50 was applied to characteristic C1 (dashed line) obtained by image processing to obtain characteristic C2 (dotted line), and the difference between the two was taken to obtain characteristic C3 (solid line), which is a short-period roughness component that excludes the long-period undulation of the bending shape of the cross section of the bending portion 10b (i.e., the shape of the circular arc on the inner side of the bending R).

[0035] The Gaussian filter is not effective at the ends of characteristic C1, and because characteristics C1 and C2 deviate as shown in Figure 4, data excluding a range of 100 μm from both ends of characteristic C3 was used to obtain the arithmetic mean roughness Ra and mean element length Rsm. Ra is twice the average value of the absolute deviation between the average line showing the average of characteristic C3 and characteristic C3 (average deviation), and Rsm is the average value of one period of the peak-to-valley interval obtained from the intersection where the roughness curve shown by characteristic C3 intersects with the average line. The minimum height that defines a peak or valley is 2 μm, and anything below 2 μm is considered noise and part of the preceding or following peak or valley.

[0036] FIG. 5 is a diagram showing the surface roughness of the inner side of the bend represented by the characteristic C3. As shown in FIG. 5, the height a and the pitch 2b are values ​​assuming that the surface roughness is a periodic unevenness, and √area in the formulas (5) and (6) is a value obtained by assuming that the surface roughness is a periodic unevenness. The cross section shown in the upper part of FIG. 5 can be replaced with the cross section shown in the lower part. As shown in FIG. 5, Ra obtained as described above corresponds to the roughness height a in the formulas (5) and (6), and Rsm corresponds to the roughness pitch 2b in the formulas (5) and (6). Therefore, Rsm and Ra can be obtained based on the image of the cross section of the bent portion 10b, and √area can be calculated based on the formulas (2) and (3).

[0037] The maximum height Rz (the difference between the height of the highest peak and the depth of the lowest valley) may be used as the roughness height a. Also, the roughness pitch 2b may be calculated by the following formula (7): s The measurement section is a 500 μm range in the center of characteristic C3. a s =0.1716·(1+120 / HV) 6 =1.05 (7)

[0038] 5. High Si type and low Si type Both the high Si type and the low Si type are made of ultra-high tensile material (DP (Dual Phase) steel) with a tensile strength of 980 MPa or more, and a Vickers hardness HV of 310 or more, preferably 340 or more. Generally, in such high strength materials, the surface roughness on the inside of the bend has a significant effect on fatigue durability, but in the high Si type and low Si type according to the present disclosure, the Si content is adjusted, and in the case of the high Si type, the n' value described later is adjusted, thereby making it an ultra-high tensile material with a better forming limit than conventional materials.

[0039] By measuring the Vickers hardness of a structural part, it is possible to determine whether the structural part is made of the ultra-high tensile material with a tensile strength of 980 MPa according to this embodiment. A method for measuring the hardness of a processed structural part for an automobile will be described using the lower arm 10 shown in Figures 1 and 2 as an example. In order to measure the hardness of the base material that has not been affected by processing, the hardness is measured at the flat plate portion 10a, which is separated from the bent portion 10b and has not been significantly distorted by the bending process.

[0040] A sample is taken with a cross section perpendicular to the surface of the flat plate portion 10a (i.e., the cross section shown in FIG. 2) as the measurement surface, and the measurement surface is prepared for hardness testing. The measurement surface is prepared in accordance with JIS Z 2244:2009. After polishing the measurement surface using silicon carbide paper of #600 to #1500, the measurement surface is mirror-finished using a diluent such as alcohol or a liquid in which diamond powder with a grain size of 1 μm to 6 μm is dispersed in pure water. The measurement surface thus mirror-finished is subjected to a hardness test according to the method described in JIS Z 2244:2009. Note that by using the cross section as the measurement surface, the influence of surface coating, etc. on the hardness measurement value can be suppressed.

[0041] Specifically, a micro Vickers hardness tester is used to measure 30 points at 1 / 4 of the plate thickness of the flat portion 10a adjacent to the bent portion 10b of the sample, with a load of 500 gf and at intervals of at least three times the indentation, and the average value is taken as the hardness of the component.

[0042] High-Si steel sheets have a microstructure composed of ferrite and tempered martensite. Ferrite is a soft layer and has advantages in n-value and uniform elongation (u-El). The n-value is correlated with uniform elongation, and high-Si steel sheets contain soft ferrite, which gives them a large hardness difference between layers (hardness difference between structures). On the other hand, low-Si steel sheets have a microstructure composed mainly of bainite (which may contain tempered martensite and ferrite), and they have a smaller hardness difference between layers (hardness difference between structures) compared to high-Si steel sheets.

[0043] In this disclosure, the high Si type and the low Si type are distinguished based on the nanoindentation hardness (hereinafter also referred to as nanohardness) measured by a nanoindentation test. More specifically, the high Si type and the low Si type are distinguished using the ratio of the interquartile range of the nanohardness to the average nanohardness (= the interquartile range of the nanohardness / average nanohardness) as a parameter indicating the work hardening ability of the material.

[0044] Fig. 6 is a histogram showing the distribution of nanohardness of the low Si type. Also, Fig. 7 is a histogram showing the distribution of nanohardness of the high Si type. In Fig. 6 and Fig. 7, the horizontal axis shows nanohardness and the vertical axis shows frequency.

[0045] The sample for measuring nanohardness is taken from the same position as that for measuring the component hardness by the Vickers hardness test described above. The measurement surface of the sample is the same as that of the Vickers hardness test. The measurement surface is mirror-finished, and the nanohardness is measured at 1 / 4 of the plate thickness. At this time, a load of 2500uN is applied, and 100 measurements are taken. The distance between indentations is ensured to be 5μm or more, and the nanohardness (i.e., indentation hardness) is calculated based on ISO14577-1 (Annex A). The interquartile range and average nanohardness are then calculated from the indentation hardness of the 100 obtained points.

[0046] The high-Si type contains soft ferrite and has a large difference in hardness between structures, so there are two nano-hardness peaks, as shown in Figure 7, and it contains a hard layer and a soft layer. The high-Si type has excellent n-value characteristics due to the inclusion of a soft layer derived from ferrite. On the other hand, the low-Si type has a small difference in hardness between structures, so there is only one nano-hardness peak, as shown in Figure 6.

[0047] FIG. 8 is a characteristic diagram showing the distribution of the uniform elongation (u-El: vertical axis) and the value obtained by dividing the interquartile range by the average nano hardness (n': horizontal axis) for the high Si type and the low Si type. The larger the value of the uniform elongation and the larger the value of n', the better the formability. In FIG. 8, the open circle (◯) indicates the high Si type and the black circle (●) indicates the low Si type. The high Si type has a higher uniform elongation, which indicates the work hardening ability, than the low Si type, but as described above, the surface roughness is relatively large due to the presence of scale derived from Si. As a result of examining the examples described later, it was found that even if the surface roughness is derived from the high Si type, if the range of formula (1) is 33≦√area≦44 and the range of formula (2) is 0.17≦r / t≦3.45, and the value of the uniform elongation is 6% or more, the surface roughness on the inside of the bend after processing is suppressed, and the fatigue properties are superior to those of the conventional product (the comparative example described later). On the other hand, in the low-silicon type, the development of microcracks on the inside of the bend is suppressed due to the small surface roughness caused by the silicon-derived scale. Therefore, by setting the range of formula (1) to 30≦√area≦40 and the range of formula (2) to 0.17≦r / t≦3.45, it is possible to achieve fatigue properties that are superior to those of conventional products, even when the uniform elongation value is less than 6%.

[0048] As shown in Figure 8, in the case of high silicon molds, when the uniform elongation of 6% or more is replaced with n' obtained from nanohardness, it becomes 0.22 or more. Measurement by tensile testing is required to determine the uniform elongation, but it is not easy to determine the uniform elongation from structural components. On the other hand, it is easy to take samples from structural components to measure nanohardness.

[0049] For this reason, in this embodiment, the characteristics of high-Si and low-Si materials are evaluated by the value n' obtained by dividing the interquartile range by the average nanohardness. For the high-Si type, n' is 0.22 or more, and for the low-Si type, n' is less than 0.22.

[0050] The high-Si type is made of DP steel with a tensile strength of 980 MPa or more, and an n' of 0.22 or more is obtained by making the Si content 0.9% or more by mass%. In this embodiment, the high-Si type is characterized by an n' of 0.22 or more, and other than this characteristic and the Si content of 0.9% or more, the chemical composition of the material and the manufacturing method are not fundamentally limited. The upper limit of the tensile strength can be applied up to about 1300 MPa. As an example, the high-Si type has the following chemical composition by mass: C: 0.01-1.0%, Si: 0.9% or more, Mn: 0.10-5.00%, P: 0.100% or less, S: 0.0300% or less, N: 0.0100% or less, O: 0-0.020%, Al: 0-1.000%, Cr: 0-2.00%, Cu: 0-2.00%, Ni: 0-2.00%, Mo: 0-3.00%, Co: 0-3.00%, Nb: 0-0.150%, V: 0-1.00%, T: 0.00% or more, and Mn: 0.00% or more. It may have a chemical composition consisting of i: 0-1.00%, W: 0-1.00%, Sn: 0-1.00%, Sb: 0-0.50%, Ta: 0-0.10%, As: 0-0.050%, B: 0-0.0100%, Ca: 0-0.100%, Mg: 0-0.100%, Zr: 0-0.100%, Hf: 0-0.100%, Bi: 0-0.100%, Zn: 0-0.200%, REM: 0-0.100%, and the balance: Fe and impurities. In the above chemical composition, the lower limit of the content of the optional added elements may be 0.0001% or 0.001%. Also usable is a steel sheet obtained by rolling steel having the above chemical composition at room temperature to 1300° C., or a steel sheet obtained by rolling and then subjecting the steel to surface treatment such as heat treatment or painting.

[0051] In the low-Si type, the surface roughness caused by the scale derived from Si can be kept small by making the Si content less than 0.9% by mass, and n' is less than 0.22. The low-Si type is characterized by n' being less than 0.22, and other than this feature and the Si content being less than 0.9%, the chemical components of the material and the manufacturing method are not fundamentally limited. The low-Si type may have the same chemical composition as the high-Si type described above, except that the Si content is less than 0.9%. In addition, similar to the high-Si type, in the above chemical composition, the lower limit of the content of the optional added elements may be 0.0001% or 0.001%, and a steel sheet obtained by rolling steel having the above chemical composition at room temperature to 1300°C, or a steel sheet obtained by rolling and then performing surface treatment such as heat treatment or painting may be used. EXAMPLES

[0052] 6. Working Example The present invention will be described in detail below with reference to examples. These examples are merely examples for confirming the effects of the present invention, and are not intended to limit the present invention.

[0053] A low-Si material having a plate thickness of 2.9 mm was bent at a radius of curvature r shown in Table 1 to produce lower arms of Comparative Examples 1 to 8 and Invention Examples 1 to 8 shown in Table 1. As shown in Table 1, Rz and Rsm were measured before and after processing by the above-mentioned method, and Rz / Rsm,√area / 2b,√area [μm] was obtained. In Invention Examples 1 to 8, √area [μm] after processing satisfies formula (1), r / t satisfies formula (2), and n' satisfies formula (3). On the other hand, Comparative Examples 1 to 8, which are conventional products, do not satisfy formula (1). As for √area, the surface roughness of the inner side of the bent portion 10b increases during processing, so the value after processing does not fall below the value before processing. In the measurement of Rz and Rsm before processing, the characteristic corresponding to the characteristic C3 in FIG. 4 can be directly obtained from the image without converting the curved surface to a flat surface.

[0054] A fatigue test was carried out on each of the lower arms of the comparative example and the invention example by applying a load in the vehicle longitudinal direction. Specifically, a load in the vehicle longitudinal direction was applied to the bent portion of each of the lower arms of the comparative examples 1 to 8 and the invention examples 1 to 8, which have different roughness parameters √area after processing, and the 200,000 cycles strength σf was measured. The 200,000 cycles strength is the load stress generated in the lower arm at 200,000 repetitions before fatigue failure occurs.

[0055] For pairs of comparative examples and examples of the invention that have the same ratio r / t of the radius of curvature inside the bend to the plate thickness, the time strength σf1 of the comparative example was compared with the time strength σf2 of the example of the invention to evaluate the fatigue durability of the example of the invention. Specifically, for each example of the invention, based on the results compared with the comparative examples, if the value of σf2 / σf1 exceeded 1.2, it was evaluated as "Good", and if the value of σf2 / σf1 exceeded 1.4, it was evaluated as "Excellent".

[0056] [Table 1]

[0057] FIG. 9 is a characteristic diagram plotting √area and r / t for each of the invention examples 1 to 8 and the comparative examples 1 to 8 shown in Table 1. In FIG. 9, the open circle (◯) indicates the invention example, and the black circle (●) indicates the comparative example. As shown in FIG. 9, the smaller the r / t, that is, the smaller the r, the larger the value of √area, and the rougher the surface roughness on the inner side of the bend becomes, and the lower the fatigue durability becomes. However, the value of √area is lower in each of the invention examples 1 to 8 than in each of the comparative examples 1 to 8 with the same r / t, and the surface roughness on the inner side of the bend is less likely to deteriorate compared to the comparative examples 1 to 8, and the surface on the inner side of the bend is smooth. Therefore, it can be seen from the results in Table 1 that the fatigue properties of the invention examples 1 to 8 are superior to those of the comparative examples 1 to 8. It can also be seen from the results in Table 1 that the larger the r and the smaller the value of √area, the better the fatigue properties become compared to the comparative examples with the same r.

[0058] In FIG. 9, characteristic C4, which is a curved approximation of the lines connecting the plots of invention examples 1 to 8, can be expressed by the following formula (8). √area=0.0976(r / t) 3 -0.7185 (r / t) 2 -1.0542(r / t)+43.426··(8)

[0059] Therefore, preferably, the structural member according to the present disclosure satisfies the following formula (9): In formula (9), a 5% margin is set as the upper limit value of √area in formula (8).

[0060] 33≦√area≦1.05{0.0976( r / t)) 3 -0.7185 (r / t) 2 -1.0542(r / t)+43.426} ··(9) [Explanation of symbols]

[0061] 10 Lower Arm 10a Flat plate part 10b Bending section 20 images

Claims

1. A structural component made of steel plate, A flat portion and a bent portion are included. A structural component, wherein the bent portion satisfies the following formulas (1), (2), and (3). 28≦√area≦45 (1) 0.17≦r / t≦6.90 (2) 0.22≦n′ (3) however, √area is the square root of the projected area of ​​the microdefect on the inside of the bent part [μm] r is the minimum value of the radius of curvature on the inside of the bend [mm] t is the thickness of the flat plate portion [mm] n' is the interquartile range of the nanohardness of the plate / mean nanohardness It is.

2. The structural part according to claim 1, further satisfying the following formula (1)' and formula (2)'. 33≦√area≦44... (1)' 0.17≦r / t≦3.45 …(2)'

3. The structural component according to claim 1 , wherein the flat portion has a Vickers hardness of 310 or more.

4. The structural component according to claim 1 , wherein the flat portion has a Vickers hardness of 340 or more.

5. The structural component according to any one of claims 1 to 4, further satisfying the following formula (4): 33≦√area≦1.05{0.0976( r / t)) 3 -0.7185 (r / t) 2 -1.0542( r / t)+43.426} ・・(4)

Citation Information

Patent Citations

  • Automotive closed section member having excellent twist fatigue characteristics

    JP2007076410A

  • Method of press-forming tubular member having special-shaped cross section and tubular member having special-shaped cross section formed by the same method

    JP2009274077A

  • Hot-rolled steel sheet

    WO2020184372A1

  • Metal forming plate, painted metal forming plate, and forming method

    JP6954211B2

  • Burring processed parts

    JP7036298B1